2017
DOI: 10.1039/c7ra00450h
|View full text |Cite
|
Sign up to set email alerts
|

A reusable surface-quaternized nanocellulose-based hybrid cryogel loaded with N-doped TiO2for self-integrated adsorption/photo-degradation of methyl orange dye

Abstract: Self-integrated adsorption/photo-degradation of methyl orange dye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…However, as stated in the introduction, the number of studies on the subject is rather limited and some of the studies used different dyes [ 19 ], which further complicates a comparison. Our data can thus only be compared to a few other datasets [ 18 , 20 , 21 , 23 ], where MO or MB was removed with different cryogels from aqueous solution. The removal rates in these studies were between 48 and 99% for both MB and MO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as stated in the introduction, the number of studies on the subject is rather limited and some of the studies used different dyes [ 19 ], which further complicates a comparison. Our data can thus only be compared to a few other datasets [ 18 , 20 , 21 , 23 ], where MO or MB was removed with different cryogels from aqueous solution. The removal rates in these studies were between 48 and 99% for both MB and MO.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly Ul’yabaeva et al [ 19 ] demonstrated the effective removal of acid yellow K with a chitosan/poly(vinyl alcohol) cryogel. Chen et al [ 20 ] demonstrated that the combination of a cryogel with a photocatalyst is an effective tool for the removal of organic dyes. Specifically, these authors produced nanocellulose cryogels with a positively charged, quaternized surface and N-doped titania for the removal and degradation of methyl orange (MO).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2017) fabricated nanofibrillated cellulose and had the surface of these nanostructures successfully functionalized with quaternary ammonium groups. Amongst the many nanofibrillated cellulose structures that had been prepared, the one endowed with nitrogendoped TiO 2 demonstrated the optimum photodegradation performance for methyl orange under simulated sunlight, despite it having not as good adsorption properties in comparison with the pristine nanofibrillated cellulose (Chen et al 2017). Besides other valuable features as an effective photodegradation catalyst, the nitrogen-doped nanofibrillated cellulose cryogel demonstrated very good reusability after multiple adsorption/photodegradation cycles and had also retained its mechanical durability and could also be recycled (Chen et al 2017).…”
Section: Titania-type Photocatalystsmentioning
confidence: 99%
“…Amongst the many nanofibrillated cellulose structures that had been prepared, the one endowed with nitrogendoped TiO 2 demonstrated the optimum photodegradation performance for methyl orange under simulated sunlight, despite it having not as good adsorption properties in comparison with the pristine nanofibrillated cellulose (Chen et al 2017). Besides other valuable features as an effective photodegradation catalyst, the nitrogen-doped nanofibrillated cellulose cryogel demonstrated very good reusability after multiple adsorption/photodegradation cycles and had also retained its mechanical durability and could also be recycled (Chen et al 2017). Yang et al (2015) reported that titanium dioxide-doped Fe 3 O 4 NPs had sufficient potential to be used as a very effective Fenton-like catalyst for dye degradation and decolouration in near neutral milieu as a result of the titanium dioxide surface doping of the iron oxide species significantly enhancing the catalytic properties of the Fe 3 O 4 in Fenton-like reactions.…”
Section: Titania-type Photocatalystsmentioning
confidence: 99%
“…Therefore, the use of TiO 2 /CNC nanocomposites can greatly reduce the energy consumption and potential hazards brought by the need for short-wavelength UV light. Table 1 illustrates the comparison of photocatalytic activities among varying TiO 2 /nanocellulose composite systems, [77][78][79][80][81][82][83][84] including TiO 2 /CNC in this work. It was found that the demonstrated TiO 2 /CNC nanocomposite possessed the smallest TiO 2 nanoparticles with high efficiency.…”
Section: Photocatalytic Antibacterial Activity and Stability Of Tio mentioning
confidence: 99%